2021
DOI: 10.3390/plants10102222
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Ambrosia trifida L. and Its Allelopathic Influence on Crops

Abstract: Phytotoxic substances released by invasive plants have been reported to have anti-pathogen, anti-herbivore, and allelopathic activity. The aim of this study was to determine the allelopathic influence of the Ambrosia trifida L. on oxidative stress parameters (the lipid peroxidation process; reduced glutathione (GSH) content; and activity of antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), and peroxidase (PX)) and phenolic compounds (total phenolic and tannin content) in maize (Zea mays L.), soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…By comparison, a statistically significant increase in MDA accumulation was recorded in the tested weeds: common lambsquarters, cockspur grass, and Johnson grass. This means that the THS provoked stress in these plants and strongly affected the lipid peroxidation [48].…”
Section: Discussionmentioning
confidence: 97%
“…By comparison, a statistically significant increase in MDA accumulation was recorded in the tested weeds: common lambsquarters, cockspur grass, and Johnson grass. This means that the THS provoked stress in these plants and strongly affected the lipid peroxidation [48].…”
Section: Discussionmentioning
confidence: 97%
“…Especially, the sesquiterpene germacrene D and the sesquiterpene lactone isabelin were able to inhibit soil-borne bacteria and even human pathogenes [24,28,35,54]. In addition, it was shown that allelochemicals, such as α/β-pinene, can induce alterations in the production of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), which plays a major role in the infection process and the subsequent bacterial differentiation into the symbiotic form [23,55,56]. In this context, also, β-caryophyllene may have an impact on the nodulation process.…”
Section: Effects On the Nodulation With Bradyrhizobium Japonicum On S...mentioning
confidence: 99%
“…Management options to effectively contain the spread of the plant are limited due to its plasticity, its highly adaptive behavior in terms of growing conditions, and its tolerance against herbicides and mechanical damage [11,[19][20][21]. Different studies on the allelopathic effects of common ragweed revealed that this plant species produces and releases several types of secondary metabolites, including the sesquiterpene ambrosic acid, phenols, thiarubrines, and thiopenes [22][23][24]. Most of these compounds have a broad spectrum of biological activities, and therefore have the potential to inhibit germination and growth of other plants and microorganisms [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many of them, for example, the Ambrosia genus, also pose a danger to human health, causing allergic reactions as well as skin and respiratory tract irritation. In addition, invasive weeds can rapidly colonize agricultural and urban lands, inhibit the growth of valuable agricultural crops (allelopathic effect), and reduce the harvest [4][5][6]. Thus, the problem of spreading these plants entails serious economic and social consequences.…”
Section: Introductionmentioning
confidence: 99%